Branding Digital Dan Identitas Budaya Yogyakarta Di Instagram @ells.picture - Hasmarini Fakhrunnisa; Rika Lusri Virga; Kurnia Indasah (ANALOGI Jurnal Ilmu Sosial dan Humaniora, 2026)
Yogyakarta is one the regions in Indonesia that has rich Javanese cultural heritage, especially traditional clothing that reflects philosophical values and cultural identity. In the era of social media, traditional culture has also become part of digital branding. The Instagram account @ells.picture present photography content featuring Yogyakarta traditional Javanese clothing in an aesthetic and modern style that attracts younger generations and tourist. This study aims to analyze how the digital branding of Yogyakarta's cultural identity is built through the representation of Javanese traditional clothing on the @ells.picture Instagram account. This study uses a qualitative approach with a descriptive method. The data collection technique was carried out through interviews, observations, and documentation of Instagram content @ells.picture. Data analysis was carried out using Stuart Hall representation theory and digital branding concepts to understand how cultural meaning is constructed through visuals, captions, and interactions on social media. The results of this study show that the Instagram account @ells.picture consistently builds digital branding through the visualization of Javanese traditional clothing that is packaged aesthetically and communicatively. Visual elements such as clothing, historical backgrounds, and poses are the main aspects in representing Javanese cultural values such as politeness, elegance, and harmony, which are then strengthened by caption that is simple and informative. Digital branding on Instagram not only increases tourist attraction, but also contributes to strengthening cultural image and supporting the promotion of culture-based tourism in the digital era.